Trend Price Analysis of Drug Before and After the Implementation of E-catalogue at the Hospital - Yusi Anggriani; Prih Sarnianto; Siti Aisyah; Jenny Pontoan (Faculty of Pharmacy, Universitas Gadjah Mada)
In 2013, Ministry of Health, Republic of Indonesia, launched a new change to drug procurement system, namely e-catalogue, to ensure the availability and affordability of medicines. This system replaces the previous auction drug procurement system. The purpose of the change into e-catalogue system is to facilitate the drug procurement in hospitals without the need to conduct complex negotiation with producers, to reduce the occurrence of mark-ups or inflating drug prices, to equalize drug prices, to support BPJS (Badan Penyelenggara Jaminan Sosial) activities, and to prevent difficulties in drug distribution in all regions in Indonesia. This study aims to get an overview and magnitude of the impact of e-catalogue application on changes in the price of drugs registered and not registered in e-catalogue at Jakarta Islamic Hospital Cempaka Putih. This research is a longitudinal time series study. The data collection was conducted retrospectively in the period of 2011-2015 taken from procurement data, purchase invoices, and e-catalogue prices from hospital pharmacy installation, which were then categorized based on similar drugs in the hospital. The result shows a decrease in the price of drugs on both e-catalogue drugs (generic, trade names and patents) and non e-catalogue drugs (generic, trade names). On the class of therapy, the biggest price reduction occurred in e-catalogue medicine, such as in antineoplastics, intravenous solution, diabetes, Anti-ashma & COPD, and psycholeptics therapy. Meanwhile, on the category of non e-catalogue, price reduction occurred in systemic antibacterials, antineoplastics, analgesics, cardiac theraphy, and A-acis A-flat A Ulcerants therapy. The magnitude of drug prices reduction ranges from 1% to more than 90% both on e-catalogue drugs and non e-catalogue drugs. On the e-catalogue drugs, the highest price reduction (82.36%) occurred in generic and patent drugs, while on non e-catalogue drugs, reduction occurred in drugs with trade names. The price reduction trend in drug prices based on both type of drugs and therapy class shows a significant decrease in drug prices in the period after the implementation of e-catalogue at Jakarta Islamic Hospital in Cempaka Putih, with a decrease of more than 80%.